The British and Soviet occupation of Iran (1941) - Soghomonyan, Hayk (YSU Journal of International Affairs, 2023)
On 25 August, 1941 British and Soviet troops invaded Iran. At the time, and for many years afterward, the main reason for this was that German influence in Iran at start of the World War 2 was noticeable. Reza Shah Pahlavi’s reliance on German technology for his ambitious development plans worried the Allies, who feared the Germans might make Iran a base for operations against the Soviet Union. In addition, in the wake of the June 1941 German invasion of the USSR, the Allies needed Iran as a channel for supplies to the Soviet Union. Furthermore, London had the defense of India in mind, and it wanted to safeguard its oilfields and refineries in Iran. Reza Shah abdicated in favor of his twenty-two year old son Mohammad Reza. In January 1942, Iran, the Soviet Union, and Britain signed the Tripartite Treaty, guaranteeing Iran’s territorial sovereignty and political independence.
Keywords: Iran; Great Britain; USSR; occupation; WW2; Reza Shah; Anglo-Iranian Oil Company